2019
DOI: 10.1038/s41401-019-0294-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel monoclonal antibody mAb109 by immuno-PET/fluorescent imaging for noninvasive lung adenocarcinoma diagnosis

Abstract: Monoclonal antibodies are believed to be magic bullets and hold great potential for lots of biological process. About 100 μg of mAb109 was expressed in 5 × 10 6 cells after 10 days’ immunization. 64 Cu-NOTA-mAb109 was synthesized with the specific activity of 0.74 MBq/μg and high in vitro stability. The binding affinity of 64 Cu-NOTA-mAb109 in A549 cells was determined to be 29.64 nM. 64 Cu-NOTA-mAb109 displayed promine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Since antibodies are already clinically available, they are relatively easy to implement as imaging agents in clinical settings. Three studies using antibodies conjugated to a NIR dye as a NIR fluorescent probe were included in this review [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since antibodies are already clinically available, they are relatively easy to implement as imaging agents in clinical settings. Three studies using antibodies conjugated to a NIR dye as a NIR fluorescent probe were included in this review [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prdx1 is overexpressed in 50–80% of all lung cancers [ 85 , 88 ]. To create a fluorescent probe, mAb109 was conjugated to the fluorophore cyanine 5.5 (Cy5.5) [ 43 ]. The probe was tested in tumor-bearing mice.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, mAb109 is a new platform for developing novel imaging agents for this type of cancer. Studies have shown that 64 Cu-NOTA-mAb109/Cy5.5-mAb109 exhibits high specificity and sensitivity for A549 tumors and human lung adenocarcinoma tissues (Zhu et al 2020 ). Furthermore, a CD146-targeting probe has been developed as a PET and NIRF imaging agent for hepatocellular carcinoma.…”
Section: Applicationsmentioning
confidence: 99%
“…Immuno-PET has the potential to revolutionize personalized medicine by enabling better patient selection for antibody-based therapies and improving drug development. Despite being relatively expensive, it has been shown in several large multi-center randomized clinical trials to be a valuable primary patient screening method that can help avoid unnecessary procedures (Zhu et al 2020 ). By providing accurate diagnoses and assisting physicians in optimizing therapeutic decisions, immuno-PET can contribute to improving clinical practice and personalized medicine.…”
Section: Applicationsmentioning
confidence: 99%
“…[ 89 Zr]Zr-daratumumab uptake has been reported in the CD38-expressing lung cancer model ( 44 ). Other probes against RTK [HER2 ( 180 ) and Axl ( 36 )] and peroxiredoxin-I, a marker of oxidative stress ( 85 ), have also been assessed in NSCLC.…”
Section: Immunopet In Different Malignanciesmentioning
confidence: 99%